A Study of distorted network : a narrative literature review analysis - Osifo, Omoregie Charles (Vaasan yliopisto, 2018)
This paper’s main objective is to study the nature and operational mode of distorted network. Network studies have become popular in many fields of social science due to different emerging global and national events. Specifically, the network theory has become a key framework in understanding and studying network and collaboration. The network theory offers holistic view on structures of interpersonal and inter-group interactions. Distorted network is a contemporary challenge, which is defined as unethical, illegal and criminal networks that exist to promote defined group objectives. Old-boy network and clandestine network are the two key types of distorted networks that exist and their operational modes also differ. A narrative literature review is adopted a strategy in analyzing selected literature on the issue of distorted network. This strategy reveals that the natures and manifestations of distorted network vary from one nation or society to another. The operational boundary of old-boy network is primarily limited to a nation state, while the operational boundary of clandestine network goes beyond a nation state (often international). The latter is justified by the ability of clandestine network to have clients and members at both home and abroad. Countries with clandestine network as main challenge tend to be more corrupt and unstable, because coercion is often adopted as a method of operation. Findings from this paper also include the difficulty to make specification on what type and operational mode of distorted network that can be found in developed or developing states/societies.
Keywords: korruptio; sosiaaliset verkostot; julkinen hallinto; fi=Julkisjohtaminen|en=Public Management|